2015
DOI: 10.1186/s12931-015-0286-3
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of USP13 mediates phenotype transformation of fibroblasts in idiopathic pulmonary fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a fatal disease characterized by fibroblastic foci and progressive scarring of the pulmonary parenchyma. IPF fibroblasts display increased proliferation and enhanced migration and invasion, analogous to cancer cells. This transformation-like phenotype of fibroblasts plays an important role in the development of pulmonary fibrosis, but the mechanism for this is not well understood.MethodsIn this study, we compared gene expression profiles in fibrotic lung tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…Unlike normal lung tissue repair, where fibroblast proliferation is self-limited, PF is characterized by uncontrolled proliferation and migration/invasion of the myofibroblasts and sustained accumulation of ECM. [ 7 ] Distinct phenotypic alterations of the fibroblasts, combined with aberrant ECM production, contribute to the development of PF. [ 8 ] Despite intensive studies, reduplicative epithelial injury along with unremitting ECM deposition seems to involve partly in lung fibrogenesis; however, the precise molecular mechanisms that modulate these processes remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike normal lung tissue repair, where fibroblast proliferation is self-limited, PF is characterized by uncontrolled proliferation and migration/invasion of the myofibroblasts and sustained accumulation of ECM. [ 7 ] Distinct phenotypic alterations of the fibroblasts, combined with aberrant ECM production, contribute to the development of PF. [ 8 ] Despite intensive studies, reduplicative epithelial injury along with unremitting ECM deposition seems to involve partly in lung fibrogenesis; however, the precise molecular mechanisms that modulate these processes remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Geng et al showed that loss of PTEN enhances aggressive phenotypes in fibroblasts, resulting in lung fibrosis (94). Interestingly, USP13 was decreased in IPF fibroblasts (94), suggesting a role of USP13 in the pathogenesis of lung fibrosis. USP13 has been shown to regulate energetic metabolism by stabilizing ATP citrate lyase and oxoglutarate dehydrogenase (95).…”
Section: Dubs That Regulate Ipf-associated Tgf-β-independent Pathwaysmentioning
confidence: 99%
“…PTEN-deficient mice exhibit increased fibroproliferation in response to bleomycin-induced lung fibrosis (93). A recent study from Geng et al showed that loss of PTEN enhances aggressive phenotypes in fibroblasts, resulting in lung fibrosis (94). Interestingly, USP13 was decreased in IPF fibroblasts (94), suggesting a role of USP13 in the pathogenesis of lung fibrosis.…”
Section: Dubs That Regulate Ipf-associated Tgf-β-independent Pathwaysmentioning
confidence: 99%
“…NLRP3 [38] Regulates NLRP3 inflammasome activation [38] NF-κB [39], NEMO [33] Regulates NF-κB signaling [33,39] VP24 [49] Involves in virus replication [49] Tat [50] Involves in virus production [50] TRAF3/TRAF6 [51] Modulates antiviral signaling [51] TRAF6/IKKγ [34] Regulates TLR signaling [34] USP-10 CFTR [37,52] Epithelial mucosal clearance [37,52] NICD1 [53] Regulates Notch signaling [53] USP-11 E2F1 [54] Regulates lung epithelia proliferation and wound healing [54] LPA1 [36] Enhances inflammation [36] USP-13 IL-1R8/Sigirr [40] Suppresses lung inflammation [40] PTEN [41] Regulates cell apoptosis [41] MCL1 [42] Regulates transformation of fibroblasts [42] STAT1 [55] Regulates IFN Signaling [55] STING [56] Negatively regulates antiviral responses [56] USP-14 I-kB [31] Increases cytokine release [31] CBP [32] Lung inflammation [32] USP-15 IκBα [57] NF-κB activation [57] USP-17 HDAC2 [58] Reverses glucocorticoid resistance [58] TRAF2/TRAF3 [59] Lung inflammation [59] [92] Inhibits type I IFN signaling and antiviral response [92] POH1 pro-IL-1β [93] Negatively regulates the immune response [93] BRCC3 NLRP3…”
Section: Dubsmentioning
confidence: 99%
“…The stability of lysophosphatidic acid receptor 1 (LPA1) is up-regulated by ubiquitin-specific protease 11 (USP11), which deubiquitinates LPA1 and enhances LPA1-mediated proinflammatory effects [ 33 , 36 , 37 , 38 , 39 ]. Furthermore, the deubiquitinating enzyme USP13 stabilizes the anti-inflammatory receptor IL-1R8/Sigirr to suppress lung inflammation [ 40 , 41 , 42 ].…”
Section: Molecular Mechanisms Of Dubs In the Pathogenesis Of Ali/amentioning
confidence: 99%